اختيار الهيكل المالي للمؤسسات المدرجة في بورصة الجزائر دراسة قياسية للفترة 2011-2013 - قدام, جمال; زيدان, محمد (جامعة الوادي University of Eloued, 2015)
يتأثر اختيار الهيكل المالي المثالي الذي يسمح بتعظيم القيمة السوقية للمؤسسة وتخفيض تكلفة التمويل بالعديد من المتغيرات المتعلقة بالخصائص المالية للمؤسسة حسب ما تفترضه نظرية العلاقة التوازنية TOT، في حين تفترض نظرية ترتيب أفضلية مصادر التمويل POT أنها ترجع للعجز التمويلي. من خلال عينة مكوٌنة من المؤسسات الأربعة المسجلة في بورصة الجزائر ولفترة ثلاث سنوات (2011 إلى 2013) توصلت الدراسة إلى أن السياسة التمويلية لهذه المؤسسات تتأثر بالاستثمارات حيث ترتكز عليها من أجل الحصول على القروض، كما يفسر العجز التمويلي الزيادة التي تحدث في نسبة الديون المالية. كما توصلت الدراسة إلى أن الجمع بين النظريتين TOT) و (POT يسمح بتفسير أكثر جودة للهيكل المالي لمؤسسات العينة. Abstract : Choosing the ideal capital structure, which allows maximizing the company’s market value and reducing the financing cost, is influenced by a set of factors related to the company’s financial characteristics as assumed by the Trade Off Theory (TOT), while the Pecking Order Theory (POT) assumes that it is due to the financing deficit. Through a sample of four companies listed on the stock exchange in Algeria for a period of three years (2011 to 2013), the study shows that the financing policy of these companies is influenced by investments where it is rely on these investments in order to get loans, as financing deficit explains the increase occurring in the financial debt ratio. The study also shows that the combination between the two theories (TOT, POT) allows more effective quality interpretation of the capital structure of the sample.
The choice of the capital structure of listed companies on the stock exchange of Algiers: econometric study of the period 2011-2013
مقال- مجلة رؤى اقتصادية
Keywords: نسبة الاقتراض، هيكل مالي، محددات الهيكل التموبلي، نظرية العلاقة التوازنية، نظرية ترتيب أفضلية مصادر التمويل; debt ratio, capital structure, determinants of the capital structure, Trade Off Theory, Pecking Order Theory.